Thermal cleaning of the paint coatings for recovering silicate municipal solid waste and the analysis of coating dissociation mechanism. (1st January 2023) - Yao, Zichun; Huang, Zhihao; Yu, Shuyuan; Zhang, Jianhao; Ma, Baoquan; Xu, Zhenming; Ruan, Jujun
Abstract: The output of waste silicate municipal solid waste represented by waste glass is huge. However, the paint coating which affects the quality of remanufactured silicate products is hazardous waste and difficult to separate from silicate resources. The aim of this study is developing new technology to clean paint coating for a more complete recycling of silicate resources and to demonstrate the effectiveness of it. Thermal cleaning technology is applied to realize the eco-friendly silicate resource recovery in this study. As a result, masses of two paint coatings have decreased by 99.42% and 68.45%. Carbon-silicon bonds formed by coupling agent is the main cause of cleaning residue. The main dissociation product of two samples is carbon dioxide, accounting for 48.83% and 84.76% respectively. Molecular dynamics simulation results show that multi-carbon groups (CC, CHCH, CC–CCH etc.) are generated in the process of thermal cleaning. Sufficient oxygen can control the conversion of these free radicals to propane, ethylene, benzene and other larger molecular. The cleaning activation energy of sample which can be completely dissociated is 132.68–167.74 kJ⋅mol −1 . The chromatic aberration between the ultra-white glass remanufactured after cleaning and the standard product is 0.9922. It is conservatively estimated that this new technology can save $207, 000 in annual decolorizer costs for traditional waste glass recycling and remanufacturing plants. Thermal cleaning can effectively reduce the loss of silicate resources during the cycle in a more environmentally friendly way. Graphical abstract: Image 1 Highlights: Novel process using thermal cleaning was proposed for silicate resource recovery. No hazardous waste solution was produced in the process of resource recovery. The best paint cleaning rate (99.42%) meets the remanufacturing requirements. Coating dissociation process was revealed by molecular dynamics. C–Si bonds formed by coupling agent was the main cause of cleaning residue.